KAJIAN CARA PERSIAPAN LAHAN DALAM USAHATANI JAGUNG DI LAHAN KERING INCEPTISOL - Azwir , (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACTLand Preparation Methods Assessment for Corn Farming System in the Inceptisol Dry Land Area. Scarcity of labor and the physical condition of the soil and the weather are series of problems in the cultivation of corn in Tanah Datar District which is one of the centers of corn production in West Sumatera. Therefore, it is necessary to find alternative ways of tillage which can save energy and cost and to conserve soil and water on dry land. The assessment has been carried out on dry land of Balimbing village, Tanah Datar District, West Sumatera from June to October 2012. The purpose of the assessment is to get the suitable method of land preparation, both technically and economically for two high yielding corn varieties in the dry lands. The assessment was carried on in a split plot design with four replications. Two varieties of corn (Bima-3 and N-35), the most prefered by farmers in the study locations serve as the main plots and three tillage methods (no-tillage/NT, minimum tillage/MT and perfect tillage/PT) as sub plots. Assessment results showed that tillage method affected the yield of corn varieties where without tillage method (TOT) gave higher yield for both varieties compared to other tillage methods. The average yield of the TOT method was 7.35 t/ha for Bima-3 variety and 7.13 t/ha for N-35 variety.Key words: Corn, dry land, land preparation, NT, MT, PT ABSTRAK Salah satu persoalan yang dihadapi usahatani jagung di lahan kering adalah permasalahan kondisi fisik tanah dan ketersediaan air yang kurang serta sulitnya tenaga kerja. Pengkajian ini bertujuan untuk mendapatkan cara persiapan lahan yang tepat baik secara teknis maupun ekonomis untuk varietas jagung yang adaptif untuk lahan kering inceptisol. Pengkajian dilakukan di lahan kering Desa Balimbing Kabupaten Tanah Datar, Sumatera Barat pada bulan Juni sampai Oktober 2012. Pengkajian dilaksanakan menurut rancangan Petak Terpisah dengan empat ulangan. Dua varietas jagung (Bima-3 dan N-35) dijadikan sebagai petak utama dan tiga sistem persiapan lahan (tanpa olah tanah/TOT, olah tanah minimum/OTM dan olah tanah sempurna/OTS) sebagai anak petak. Hasil pengkajian menunjukkan bahwa cara persiapan lahan berpengaruh terhadap hasil jagung varietas Bima-3 dan N-35. Cara persiapan lahan dengan tanpa olah tanah (TOT) memberikan hasil relatif lebih tinggi untuk kedua varietas dibanding dengan cara persiapan lahan lain, yaitu untuk varietas Bima-3 7,35 t/ha dan untuk N-35 7,13 t/ha. Oleh karena itu, kedepan pengembangan jagung di lahan kering Inceptisol dapat digunakan kombinasi varietas Bima-3 dengan cara persiapan lahan TOT. Kata kunci: Jagung, lahan kering, OTS, OTM, TOT